he Psychic Anorexia: Analysis of Decision-Making Processes - Shepetovska, Eva Malgorzata (Psychological Prospects Journal, 2013)
The clinical research of women suffering from anorexia nervosa has shown thinking disorders. These disorders are manifested as the incorrect decisions in the tasks including food and appearance. The research of anorexic and health ща women was conducted to test this thesis. The aim of analysis was the assessment of strategies of decision making process in two situations: choice of a holiday offer, choice of an assistant offer. Women attending in research had to control 2 types of hints – the value of main elements of each offer (opinion 1–5) and the meaning of hints, to choose an offer as best as it could be. Statistical analysis included the number of open fields in both types of tasks, time of accomplishment the tasks, types of strategies and the accuracy of choices.